High levels of FAD autofluorescence indicate pathology preceding cell death - Bryanskaya, Ekaterina O.; Vinokurov, Andrey Y.; Dolgikh, Angelina I.; Dunaev, Andrey V.; Angelova, Plamena R.; Abramov, Andrey Y. (Biochimica et biophysica acta. General subjects, 2024)
Flavin adenine dinucleotide (FAD) autofluorescence from cells reports on the enzymatic activity which involves FAD as a cofactor. Most of the cellular FAD fluorescence comes from complex II of the electron transport chain in mitochondria and can be assessed with inhibitor analysis. The intensity of FAD autofluorescence is not homogeneous and vary between cells in tissue and in cell culture types. Using primary co-culture of neurons and astrocytes, and human skin fibroblasts we have found that very high FAD autofluorescence is a result of an overactivation of the mitochondrial complex II from ETC and from the activity of monoamine oxidases. Cells with high FAD autofluorescence were mostly intact and were not co-labelled with indicators for necrosis or apoptosis. However, cells with high FAD fluorescence showed activation of apoptosis and necrosis within 24 h after initial measurements. Thus, high level of FAD autofluorescence is an indicator of cell pathology and reveals an upcoming apoptosis and necrosis.